Effect of initial support particle size of MnOx/TiO2 catalysts in the selective catalytic reduction of NO with NH3. Issue 9 (6th February 2019) - Yang, Yang; Hu, Zhun; Mi, Rongli; Li, Dan; Yong, Xiang; Yang, Huie; Liu, Kunfeng
Abstract : Support particle size could influence the surface Mn 4+ /Mn ratio of catalysts, promoting the reactivity of bridge nitrate, therefore enhancing SCR performance. Abstract : A series of manganese-based catalysts supported by 5–10 nm, 10–25 nm, 40 nm and 60 nm anatase TiO2 particles was synthesized via an impregnation method to investigate the effect of the initial support particle size on the selective catalytic reduction (SCR) of NO with NH3 . All catalysts were characterized by transmission electron microscopy (TEM), N2 physisorption/desorption, X-ray diffraction (XRD), temperature programmed techniques, X-ray photoelectron spectroscopy (XPS) and in situ diffuse reflectance infrared transform spectroscopy (DRIFTS). TEM results indicated that the particle sizes of the MnO x /TiO2 catalysts were similar after the calcination process, although the initial TiO2 support particle sizes were different. However, the initial TiO2 support particle sizes were found to have a significant influence on the SCR catalytic performance. XPS and NH3 -TPD results of the MnO x /TiO2 catalysts illustrated that the surface Mn 4+ /Mn molar ratio and acid amount could be influenced by the initial TiO2 support particle sizes. The order of surface Mn 4+ /Mn molar ratio and acid amount over the MnO x /TiO2 catalysts was as follows: MnO x /TiO2 (10–25) > MnO x /TiO2 (40) > MnO x /TiO2 (60) > MnO x /TiO2 (5–10), which agreed well with the order of SCR performance. In situ DRIFTS results revealed that the NH3 -SCR reactions over MnO x /TiO2 at low temperature occurred via a Langmuir–Hinshelwood mechanism. More importantly, it was found that the bridge and bidentate nitrates were the main active substances for the low-temperature SCR reaction, and bridge nitrate adsorbed on Mn 4+ showed superior SCR activity among all the adsorbed NO x species. The variation of the initial TiO2 support particle size over MnO x /TiO2 could change the surface Mn 4+ /Mn molar ratio, which could influence the adsorption of NO x species, thus bringing about the diversity of the SCR catalytic performance.